Virtual tour video project in Japanese for tourism class - Arianingsih, Anisa; Syihabuddin, Syihabuddin (Japanese Research on Linguistics, Literature, and Culture, 2022)
This study aims to describe the implementation procedure of the Virtual Tour Video Project as a learning method in Japanese for Tourism classes and students’ responses to this project. This research used a descriptive method, and the research instrument is a questionnaire. The sample of this research is 12 students of the 5th semester Japanese Department of UNIKOM in the 2021/2022 academic year. The results show that the student's response in working on this project was obtaining a percentage value of 82.2%. Although some difficulties are encountered in the process, such as searching for material, translating into Japanese, and utilizing technology, this project has many benefits. Virtual Tour Video Project is one alternative method that can be used in Japanese class, especially Japanese for Tourism.